Análisis comparativo de la aplicación de controladores en un proceso embebido de temperatura. - Remache Coyago, Juan Carlos (2023)
Temperature is one of the variables always present in the industry and when trying to carry out a control practice, there are two difficulties: finding a mathematical model of the plant that presents certain accuracy and testing the controller or controllers designed with the physically available plant in order to stabilize the output variable. Currently, the hardware of industrial PLCs also allows software with instructions to implement a type of advanced control, however, their cost is high. The new technologies have made it possible to have free, low-cost hardware on the market, but the implementation of the algorithm for digital control in them is still under development and there are some failures in the display of results in several cases. This titling project implements an embedded temperature process based on the characteristics of the TIP31C transistor and the LM35 sensor, the controller used is based on the Arduino card where the algorithms for PID and Fuzzy digital control are developed. The Simulink tool is used as advanced software for the identification of the mathematical model of the plant, the collection and storage of data, and through the libraries a screen with programming blocks is created for the graphic display of process variables and the calculation of indices. error-based performance.